2008
DOI: 10.1152/ajpheart.01365.2007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for functional alterations in the skeletal muscle mechanoreflex and metaboreflex in hypertensive rats

Abstract: Leal AK, Williams MA, Garry MG, Mitchell JH, Smith SA. Evidence for functional alterations in the skeletal muscle mechanoreflex and metaboreflex in hypertensive rats. Am J Physiol Heart Circ Physiol 295: H1429 -H1438, 2008. First published July 18, 2008 doi:10.1152/ajpheart.01365.2007.-Exercise in hypertensive individuals elicits exaggerated increases in mean arterial pressure (MAP) and heart rate (HR) that potentially enhance the risk for adverse cardiac events or stroke. Evidence suggests that exercise pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
69
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 52 publications
19
69
2
3
Order By: Relevance
“…Based on the present results, we suggest that increased RAAS activity in hypertension sensitizes mechanically sensitive muscle afferents responding to contraction by inducing oxidative stress in the muscle. Mechanosensitive muscle afferent sensitization in hypertension has been suggested by the previous SHR studies reporting that RSNA and cardiovascular responses to stretch of the Achilles tendon, a maneuver that selectively excites mechanically sensitive muscle afferents, were excess in SHRs (24,37), and that the exaggerated responses to continuous contraction of hindlimb skeletal muscle in SHRs were reduced to a large degree (about half) by intra-arterial injection into the hindlimb circulation of gadolinium, a mechanoreceptor blocker (15,37).…”
Section: H148mentioning
confidence: 97%
See 1 more Smart Citation
“…Based on the present results, we suggest that increased RAAS activity in hypertension sensitizes mechanically sensitive muscle afferents responding to contraction by inducing oxidative stress in the muscle. Mechanosensitive muscle afferent sensitization in hypertension has been suggested by the previous SHR studies reporting that RSNA and cardiovascular responses to stretch of the Achilles tendon, a maneuver that selectively excites mechanically sensitive muscle afferents, were excess in SHRs (24,37), and that the exaggerated responses to continuous contraction of hindlimb skeletal muscle in SHRs were reduced to a large degree (about half) by intra-arterial injection into the hindlimb circulation of gadolinium, a mechanoreceptor blocker (15,37).…”
Section: H148mentioning
confidence: 97%
“…This muscle-based reflex is termed the exercise pressor reflex (35). A series of studies by Smith and colleagues (24,37,38,43) using a decerebrate rat preparation has suggested that in spontaneous hypertensive rats (SHRs), both mechanically and chemically sensitive muscle afferents engaged during skeletal muscle contraction are stimulated excessively compared with those in normotensive rats, thereby evoking exaggerated sympathoexcitatory and pressor responses to contraction. In humans with hypertension, the elevation in muscle sympathetic nerve activity seen during postexercise ischemia, a maneuver that selectively excites chemically sensitive muscle afferents, was higher than that in normotensive subjects (10).…”
mentioning
confidence: 99%
“…The rationale for these additional experiments was that 1) stimulation of mechanically sensitive afferent fibers can be readily induced by stretching skeletal muscle lending itself to a 30-s "stimulation/relaxation" protocol, and 2) the mechanoreflex component of the EPR has recently been shown to be dysfunctional in hypertension, producing elevated increases in ABP and sympathetic nerve activity (13,23). In a separate group of animals (WKY n ϭ 10; SHR n ϭ 11) than those in which muscle contraction was evoked, mechanically sensitive afferent fibers were preferentially stimulated by passively stretching the soleus and gastrocnemius muscles of the right hindlimb using a calibrated 9.5-mm rack and pinion system (Harvard Apparatus).…”
Section: Protocol 2: Mechanoreflex Testingmentioning
confidence: 99%
“…Activation of the EPR, a reflex originating in skeletal muscle, is mediated by stimulation of mechanically sensitive receptors located primarily on group III afferent fibers and metabolically sensitive receptors located primarily on group IV afferent fibers (10,11). In hypertension, combined or individual activation of either the mechanical (i.e., mechanoreflex) or metabolic component (i.e., metaboreflex) of the EPR results in a heightened sympathetically mediated cardiovascular response (2,13,22,23,34,38). To date, however, the mechanisms underlying EPR overactivity in hypertension remain largely unknown.…”
mentioning
confidence: 99%
“…2). Then, Leal et al 85) showed that pressor responses to either passive muscle stretch or intra-arterial infusion of capsaicin into hindlimb circulation were greater in SHR, suggesting that the exaggerated EPR in hypertension is mediated by both mechanoreflex and metaboreflex overactivity (Fig. 2).…”
Section: Contribution Of Rat Studies To Understanding Of Mechanisms Umentioning
confidence: 99%